2020
DOI: 10.3390/su12187795
|View full text |Cite
|
Sign up to set email alerts
|

The Jungle of Support: What Do We Really Mean When We Say “Residents’ Support”?

Abstract: The aim of this research is to provide a conceptual framework to facilitate the standardization of the concept of “residents’ support” in tourism studies. The model is designed to prevent ambiguity and confusion that may arise in the use of the generic term “residents’ support.” Social Exchange Theory and the Theory of Reasoned Action will be incorporated for the purposes of contextualizing the term “residents’ support” with respect to three dimensions: attitudinal, intentional, or behavioral. A longitudinal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…The findings of this study have practical implications for local authorities when planning, designing, and implementing future tourism development ideas in the wetland area [156]. They suggest that monitoring residents' attitudes is important if authorities are determined to work with policies that would maximize the benefits of tourism development and minimize the negative impacts [68,155].…”
Section: Discussionmentioning
confidence: 86%
“…The findings of this study have practical implications for local authorities when planning, designing, and implementing future tourism development ideas in the wetland area [156]. They suggest that monitoring residents' attitudes is important if authorities are determined to work with policies that would maximize the benefits of tourism development and minimize the negative impacts [68,155].…”
Section: Discussionmentioning
confidence: 86%
“…They are well known and tend to be the most impressive to tourists and have become the first choice for people to experience the customs of ethnic minorities in Guizhou. Other specific features frequently cited in the blogs were Gulou (drum-tower, n = 92), Diaojiaolou (pile dwellings, 78), culture (73), nationality (72), inn (59), Zhaizi (stockade village, 57), terraces (53), and architecture (46). This demonstrated that tourists had a high degree of recognition of the unique characteristics, structures, and living conditions of these Guizhou ethnic minorities.…”
Section: Tourist Perceptionsmentioning
confidence: 90%
“…On the demand side, perceived value research involves consumer perceptions of service quality and the value of cultural products [46]; relationships among the influencing factors of purchases and motivation [47]; motivations and development strategy of villages [48]; differences in tourist perceived value [49,50]; and public perceived value [51]. Su et al [52] found that ethnic encounters were not perceived by tourists as a primary motivation to visit ethnic minority villages, but residents' support, including attitude support (AS), intention support (IS), and behavioral support (BS) [53] could contribute to the formation of satisfactory on-site experiences. Perceptual images of specific cases have been determined.…”
Section: Tourist Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a given community, the impact of people's familiarity with the environment and long-term interaction cannot be ignored. The resident can favor or hinder the future of tourism in a region with his/her actions [69]. "Villagers" should also become an important part of the aesthetic experience since they not only provide grass-roots services for tourists, but also need to participate in tourism development, give full play to the interactivity between villagers and the environment, and show the practical interactions of unique products, livelihoods [70], and farming culture to provide tourists with a deeply immersive and satisfying aesthetic experience.…”
Section: Key Factors But Low Satisfactionmentioning
confidence: 99%